Assessment of analytical techniques for characterization of crystalline clopidogrel forms in patent applications - Luiz Marcelo Lira; Alexandre Lopes Lourenço; Guilherme Ferreira Neves; Valéria Pereira de Sousa; Carlos Rangel Rodrigues; Lúcio Mendes Cabral (Universidade de São Paulo, 2014)
The aim of this study was to evaluate two important aspects of patent applications of crystalline forms of drugs: (i) the physicochemical characterization of the crystalline forms; and (ii) the procedure for preparing crystals of the blockbuster drug clopidogrel. To this end, searches were conducted using online patent databases. The results showed that: (i) the majority of patent applications for clopidogrel crystalline forms failed to comply with proposed Brazilian Patent Office guidelines. This was primarily due to insufficient number of analytical techniques evaluating the crystalline phase. In addition, some patent applications lacked assessment of chemical/crystallography purity; (ii) use of more than two analytical techniques is important; and (iii) the crystallization procedure for clopidogrel bisulfate form II were irreproducible based on the procedure given in the patent application.